Implementasi Model Problem Based Learning Berbantuan Media Audiovisual pada Materi Siklus Air di Kelas V SDN 5 Kampung Baru - Agustina, Eka (Ibtida'i, 2022)
Abstract. One of the learning models that can be applied in the 2013 curriculum is the problem based learning (PBL) learning model, which is a learning model characterized by real problems as a context for students to gain knowledge by solving problems given by the teacher. Where the PBL model has been applied in SD Negeri 5 Kampung Baru using audiovisual media. This study aims to determine the planning, implementation and assessment using the PBL learning model assisted by audiovisual media on the water cycle material for class V SD Negeri 5 Kampung Baru. Sources of data in the study were teachers and students of class V SD Negeri 5 Kampung Baru. The research method used is descriptive qualitative. The results of the study indicate that: Planning is done by setting learning objectives, learning models, learning media, learning resources and assessments that are used as one forum, namely RPP. The implementation of learning has been in accordance with the steps of the PBL model. The assessment is based on the authentic assessment of the 2013 curriculum which includes aspects of attitudes, knowledge and skills. It can be concluded that the teacher has implemented learning using the PBL model assisted by audiovisual media in accordance with the theory. However, there are shortcomings in planning and assessment, namely the teacher has not used the rubric of the assessment instrument contained in the teacher's book so that the teacher does not understand the extent to which the ability of students to understand the material that has been delivered. Keywords: Problem Based Learning model, audiovisual media.